'Happy to have been of service': The Yale archive as a window into the engaged followership of participants in Milgram's 'obedience' experiments. (5th September 2014) - Haslam, S. Alexander; Reicher, Stephen D.; Millard, Kathryn; McDonald, Rachel
<x xml:space="preserve">Abstract</x> This study examines the reactions of participants in Milgram's 'Obedience to Authority' studies to reorient both theoretical and ethical debate. Previous discussion of these reactions has focused on whether or not participants were distressed. We provide evidence that the most salient feature of participants' responses – and the feature most needing explanation – is not their lack of distress but their happiness at having participated. Drawing on material in Box 44 of Yale's Milgram archive we argue that this was a product of the experimenter's ability to convince participants that they were contributing to a progressive enterprise. Such evidence accords with an engaged followership model in which (1) willingness to perform unpleasant tasks is contingent upon identification with collective goals and (2) leaders cultivate identification with those goals by making them seem virtuous rather than vicious and thereby ameliorating the stress that achieving them entails. This analysis is inconsistent with Milgram's own agentic state model. Moreover, it suggests that the major ethical problem with his studies lies less in the stress that they generated for participants than in the ideologies that were promoted to ameliorate stress and justify harming others.